2001
DOI: 10.1006/mthe.2001.0268
|View full text |Cite
|
Sign up to set email alerts
|

Streptavidin Paramagnetic Particles Provide a Choice of Three Affinity-Based Capture and Magnetic Concentration Strategies for Retroviral Vectors

Abstract: Three strategies have been designed to concentrate infectious retroviral vectors from the supernatants of human- (HT1080) and murine- (NIH 3T3) based packaging cells. Streptavidin-conjugated paramagnetic particles in conjunction with (i) antibodies directed against murine fibronectin, (ii) biotinylated lectins, or (iii) biotin-modified packaging cell-surface proteins allow affinity-mediated magnetic concentration of retroviral vectors. Retroviral titers (assayed by colony formation of human myeloid K562 cells)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
71
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(73 citation statements)
references
References 39 publications
2
71
0
Order By: Relevance
“…The size and surface chemistry of magnetic particles can be tailored to meet specific demands on physical and biological characteristics, also the linkage between vector and magnetic particle can be designed accordingly. This conclusion is in accordance with parallel work by Hughes et al, 19 who most recently attached retroviral vectors via biologic linkage to commercially available magnetic microbeads. These authors demonstrated a similarly encouraging improvement in vector targeting and efficacy by magnetic force as we found for any vector type in a less sophisticated approach.…”
Section: Discussionsupporting
confidence: 91%
“…The size and surface chemistry of magnetic particles can be tailored to meet specific demands on physical and biological characteristics, also the linkage between vector and magnetic particle can be designed accordingly. This conclusion is in accordance with parallel work by Hughes et al, 19 who most recently attached retroviral vectors via biologic linkage to commercially available magnetic microbeads. These authors demonstrated a similarly encouraging improvement in vector targeting and efficacy by magnetic force as we found for any vector type in a less sophisticated approach.…”
Section: Discussionsupporting
confidence: 91%
“…The procedure reported by Hughes et al (2001) was followed as summarised in Figure 1. Briefly, on Day 1 of a given experiment 1x10 6 PG13.pBabe.puro cells were seeded onto a 9cm diameter round plate in 15mL Dulbecco's modified Eagle's medium (DMEM) supplemented with 10% foetal calf serum (FCS), 2 mM L-glutamine, 100 µg/mL streptomycin, and 100 U/mL penicillin.…”
Section: Methodsmentioning
confidence: 99%
“…However, in other therapeutic contexts, complexing viral vectors within polysaccharide scaffold mimics of the extracellular matrix has proven advantageous for transduction of target cells (Thomas andShea 2013, Sun et al 2014) Le Doux et al (1999) previously reported that hyaluronan inhibits retroviral transduction. However, Hughes et al (2001) showed that paramagnetic particles coated with antibodies to the extracellular matrix component, fibronectin, could capture retrovirus particles secreted from the fibroblast-derived packaging cell line, PG13.pBabe.puro (Miller et al 1991). Fibronectin and hyaluronan are believed to interact extensively to define extracellular matrix behaviour in normal and cancerous tissues (Evanko et al 2015).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations